Pengaruh Intensitas Penggunaan Artificial Intelligence (AI), Literasi Digital, dan Kreativitas Terhadap Etika Belajar Mahasiswa Melalui Motivasi Belajar Sebagai Variabel Mediasi - Ahmad Ihsanul Anhar; Dwi Wahyu Artiningsih; Basuki Basuki (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the impact of Artificial Intelligence (AI) usage intensity, digital literacy, and creativity on student learning ethics, with learning motivation as a mediating variable among UNISKA MAB Banjarmasin students in the 2024/2025 academic year. In the digital era, education increasingly relies on technological innovation, requiring students to balance digital competence with ethical learning behavior such as discipline, respect, and responsibility. The research employs a quantitative explanatory approach to explore cause-and-effect relationships, involving 96 proportional samples from a total population of 1,999 students. Data analysis was conducted using SmartPLS Version 4. The results indicate that AI usage intensity has a positive but insignificant effect on learning ethics (p = 0.374), while digital literacy shows a strong and significant positive impact (p = 0.040). Creativity has a positive yet insignificant effect (p = 0.669), whereas learning motivation has a strong and significant influence on learning ethics (p = 0.000). Furthermore, AI usage through learning motivation shows a negative but insignificant effect (p = 0.903), digital literacy through learning motivation shows a positive but insignificant effect (p = 0.065), and creativity through learning motivation demonstrates a strong and significant positive effect (p = 0.000). These findings highlight learning motivation as a key factor linking creativity and ethical learning behavior in the digital age.